2017
DOI: 10.1186/s12947-017-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative single ventricle function determines early outcome after second-stage palliation of single ventricle heart

Abstract: BackgroundSecond-stage palliation with hemi-Fontan or bidirectional Glenn procedures has improved the outcomes of patients treated for single-ventricle heart disease. The aim of this study was to retrospectively analyze risk factors for death after second-stage palliation of single-ventricle heart and to compare therapeutic results achieved with the hemi-Fontan and bidirectional Glenn procedures.Material and methodsWe analyzed 60 patients who had undergone second-stage palliation for single-ventricle heart. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
0
5
1
Order By: Relevance
“…Several studies have reported >70% survival rates. [6][7][8][9][10][11][12][13] In contrast, operative mortality was very high in this study. Most of the deaths in our study occurred during hospitalization at stage I, mainly in patients who underwent BTS.…”
Section: Commentcontrasting
confidence: 67%
See 3 more Smart Citations
“…Several studies have reported >70% survival rates. [6][7][8][9][10][11][12][13] In contrast, operative mortality was very high in this study. Most of the deaths in our study occurred during hospitalization at stage I, mainly in patients who underwent BTS.…”
Section: Commentcontrasting
confidence: 67%
“…1,3,4 Single ventricle physiology, one of the main complex CHD types, requires early detection and referral to a pediatric cardiac center. 6,7 The surgical treatment of these patients usually requires more than two palliative procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Recent studies have investigated the impact of single patient factors on survival, including nutritional status, lower birth weight, weight at surgery, ventricular dominance, Blalock-Taussig shunt versus right ventriculotomy for right ventricular to pulmonary artery shunt, shunt fraction, ventricular function, hybrid versus Norwood procedure, genetic abnormality, extracorporeal membrane oxygenation, and open sternum on the day of the Norwood procedure. [9][10][11][12][13][14][15] Patient factors, however, are not solitary but coexist in a complex interplay that affects survival. Do et al utilized a neural network to identify multiple factors together that are predictive of 1-year survival.…”
mentioning
confidence: 99%